Virtual experience camp in children - Ángela Figueroa Sobrero (Revista de la Sociedad Argentina de Diabetes, 2022)
Recreational educational camps are an important tool to improve knowledge in children with type 1 diabetes (T1D). Group education stimulates self-confidence, self-care and progressive autonomy, in addition to interpersonal relationships with peers, and reinforcement of patient-doctor-health team links.